IPTEKS PENGHITUNGAN RISIKO PASAR DALAM KEPUTUSAN INVESTASI - Pontoh, Winston; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2019)
Well-established life is a common objective of people, and in term of to reach that objective then most of people should utilize knowledge and skills. One of the effort of people is normally make an investment especially stock investment. One of the reference for investors in case to make stock investments is market risk. Stock beta is one of market risk representative which measures stock responsiveness on market movements and capital asset pricing model (CAPM) is one method to measure market risk.